Absalom, Absalom! : the corrected text - Faulkner, William, 1897-1962 (Random House, 1986)
The story of Thomas Sutpen, an enigmatic stranger who came to Jefferson in the early 1830s to wrest his mansion out of the muddy bottoms of the north Mississippi wilderness. He was a man, Faulkner said, "who wanted sons and the sons destroyed him."